Ethical procedures in scientific research - Rodrigues, Liliana (2023)
This work has as its theme the ethical procedures of research and aims to provide a framework of practical guidelines to ensure the protection of all actors involved in the development of scientific knowledge, particularly at the stage of research design and project. This is a theoretical reflection on the ethical dimension of data collection practices and the limits that the researcher should consciously attend to in the scientific research process. For this reflection, I carried out a literature review and a document analysis of several legal documents, highlighting the European directive on data protection. This led to several questions, namely: what documents should be ensured in the research project design process? What is the scope of informed consent and how can anonymity and confidentiality of data be preserved? These and other questions are answered in a thoughtful way for those who understand that there is no science without ethics, nor ethics without conscience. Here the hermeneutic method is the natural choice because it allows the interpretation of questions related to values and principles that must be contextualized. This interpretative analysis requires asking questions related to duty, but also to the norm or law. With this questioning it is hoped that the reader will understand in a systematized way the ethical procedures of research and will be able to draw on a documentary listing of the ethical point of view that will protect the informants, but also the researcher himself and affiliating institutions or participants.